Analysis of the Influence of Paddy Prices and Rice Production on the Farmers’ Terms of Trade of Food Crops in West Sumatra - Muhammad Farrel Syabena; Syahyana Raesi; Hadi Prastyo; Abil Fadila; Saedi Bawana (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2026)
The agricultural sector plays a strategic role in improving farmers’ welfare, particularly in the food crops subsector where rice remains Indonesia’s main staple. The Farmers’ Terms of Trade is widely used as an indicator to measure farmers’ welfare by reflecting their purchasing power. This study aims to analyze the effect of paddy prices and rice production on the Farmers’ Terms of Trade in the food crops subsector in West Sumatra Province. This research uses secondary time series data from 2015 to 2024 obtained from official statistical sources. The analysis applies a multiple linear regression model supported by classical assumption tests to ensure the validity of the results. The findings indicate that paddy prices and rice production simultaneously have a significant effect on Farmers’ Terms of Trade. Partially, paddy prices have a positive and significant effect, indicating that increases in paddy prices directly improve farmers’ welfare. In contrast, rice production has a positive but not significant effect on Farmers’ Terms of Trade, suggesting that higher production does not necessarily improve farmers’ welfare due to production instability, declining harvested areas, and increasing production costs. The model explains 61.4% of the variation in Farmers’ Terms of Trade. These results imply that improving farmers’ welfare requires not only increasing production but also ensuring price stability and enhancing production efficiency. Therefore, policies should focus on stabilizing paddy prices and promoting sustainable agricultural practices.